Nucleotide sequence at the end of the gene for the RNA polymerase beta' subunit (rpoC). - Squires, C (1981)
We have determined the DNA sequence surrounding the transcription terminator following rpoC, the gene that codes for the beta' subunit of RNA polymerase in E. coli K12. The 2044 bp sequence obtained contains the distal 335 codons of rpoC followed by a 212 bp non-coding region and a second open reading frame (ORFa) of 179 codons. The final 181 nucleotides of the sequence form the 5' end of a third open reading frame (ORFb). The in vivo 3' end of the rpoC mRNA was located by analysis of RNA/DNA hybrids cleaved with nuclease S1 (S1 mapping). These results indicated that the major transcription termination of the rplJL-rpoBC transcription unit occurs a short distance past the translation stop codon for rpoC. Four regions of symmetry, suggesting secondary structure in the mRNA, were found in the DNA sequence near the rpoC translation termination codon. The last of these hairpin structures is similar to other rho-independent transcription terminators and its 3' end coincides with the end of the rpoC mRNA as predicted by S1-mapping. Inspection of the open reading frames indicates that rpoC uses a high percentage of codons that are recognized by the major tRNA species of E. coli while ORFa and ORFb contain many codons recognized by minor tRNA species. ORFa specifies a very basic peptide.